Effect of Mirtazapine Pre-treatment on Haloperidol, Ergometrine and Fluoxetine Induced Behaviours in Albino Rats - Vandana M. Thorat; Chitra C. Khanwelkar; Somnath M. Matule; Pratibha S. Salve; Smita A. Surle-Patil; S. Seshla (Journal of Krishna Institute of Medical Sciences University)
Background: Central 5-HT2A and 5-HT2C serotonergic receptors are mainly involved in the control of nigrostriatal and mesolimbic dopaminergic neuronal activity has been well proved and established. 5-HT has facilitatory effect on stimulated dopamine release by stimulating central 5-HT2A receptors and inhibitory effect by stimulating 5-HT2C receptors. Aim and Objectives: To evaluate 5-HT2A and 5-HT2C receptor blocking activity of Mirtazapine (MIR) and the effect of mirtazapine pre-treatment on Ergometrine (ERG) induced behaviours, Fluoxetine (FLU) induced penile erections and Haloperidol (HAL) induced catalepsy in rats. Material and Methods: Each group was subdivided into different subgroups consisting 6 animals in each. Control group received Dimethyl Sulfoxide (DMSO) and other groups received different doses of mirtazapine one hour before ERG/FLU/HAL. Values obtained from control group were compared with all remaining groups pre-treatment with different doses of MIR. Results: MIR (MIR) at 2.5, 5, 10 and 20 mg/kg intraperitoneally (i.p) did not produce any per se effects. Pre-treatment with 5, 10 and 20 mg/kg i.p. MIR significantly antagonised ERG induced behaviours. 5 mg/kg i.p. MIR significantly antagonised whereas 10 and 20 mg/kg i.p. MIR abolished FLU (10 mg/kg) induced penile erections in rats. MIR 5 and 20 mg/kg i.p. significantly antagonised HAL (1mg/kg) induced catalepsy at 1 hr testing time interval while 10 and 20 mg/kg MIR significantly antagonised HAL (1 mg/kg) induced catalepsy at 2 hr testing time interval. Conclusion: Our results indicate that MIR at 5, 10 and 20 mg/kg possesses 5-HT2A and 5-HT2C receptors blocking activity. At 5, 10 and 20 mg/kg MIR, by blocking central 5-HT2C receptors predominantly, causes release of dopamine from nigrostriatal dopaminergic neurons and therefore antagonizes HAL induced catalepsy.